Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. Global Teknomedika Mandiri Pekanbaru - Ikhsan, Wandi Nur; Vionita, Deby Oksari (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research was conducted at PT. Global Teknomedika Mandiri Pekanbaru, the employees studied were 31 people. The purpose of this study was to determine the effect of Work Motivation on Employee Performance at PT. Global Teknomedika Mandiri Pekanbaru with the results of the partial test obtained a t-count value of 7.754 while the t-table value was 2.045. This explains that t-count (7.754)> t-table (2.045) with sig 0.000 <sig 0.05, so it can be concluded that there is a significant influence on Work Motivation on Employee Performance at PT. Global Teknomedika Mandiri Pekanbaru. While the calculation of the Determination coefficient (R2) is known that the R Square value is 0.675. This shows that the Work Motivation variable as a whole has an influence of 67.5% on Employee Performance while the remaining 32.5% is influenced by other variables not examined in this study, for example: Incentives, Work Discipline. The conclusion of this study is that the results of the study prove that Work Motivation on Employee Performance at PT. Global Teknomedika Mandiri Pekanbaru is proven to be valid and reliable.